2002
DOI: 10.1007/s001220100751
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis in the genus Cicer and cultivated chickpea using RAPD and ISSR markers

Abstract: Seventy five accessions belonging to 14 species of the genus Cicer were analysed with PCR-based molecular markers to determine their phylogenetic relationships. Eight of the species were annuals and included the Section Monocicer which contains cultivated chickpea ( Cicer arietinum L.). The remaining six species were perennials (five from Section Polycicer and one from Section Acanthocicer). More than one accession per species was analysed in most of the wild species; within C. arietinum, 26 accessions includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
106
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 29 publications
31
106
6
1
Order By: Relevance
“…In this study, we have compared the marker data-sets produced using morphological and three different marker systems, ISSR, DAMD and SCoT, to define genetic relationships within a set of 40 genotypes representing different geographical areas of north-west of Iran, and to know if these marker systems can be effectively used in breeding programme. We found relatively acceptable genetic diversity within available Iranian landrace chickpea accessions which is contrary to the findings of Iruela et al (2002), who reported low level of genetic diversity within C. arietinum compared to the wild species. In present study, the genotypes were selected based on the presence or absence of field resistance to Ascochyta blight, cold (data not presented), drought and some morphological traits and differences in source of collection.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, we have compared the marker data-sets produced using morphological and three different marker systems, ISSR, DAMD and SCoT, to define genetic relationships within a set of 40 genotypes representing different geographical areas of north-west of Iran, and to know if these marker systems can be effectively used in breeding programme. We found relatively acceptable genetic diversity within available Iranian landrace chickpea accessions which is contrary to the findings of Iruela et al (2002), who reported low level of genetic diversity within C. arietinum compared to the wild species. In present study, the genotypes were selected based on the presence or absence of field resistance to Ascochyta blight, cold (data not presented), drought and some morphological traits and differences in source of collection.…”
Section: Discussioncontrasting
confidence: 99%
“…The assessment of genetic diversity is important not only for crop improvement but also for efficient management and conservation of germplasm resources. DNA-based molecular markers such as random amplified polymorphic DNA (RAPD; Iruela et al 2002;Talebi et al 2008a) and RFLP (Powell et al 1996) were unable to address the reliable genetic variation within chickpea (Saeed et al 2011). Genetic fingerprinting in chickpea, for a long time hampered by the little variability in chickpea's genome, can be facilitated by highly polymorphic functional markers such as SCoT and DAMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For efficient and effective germplasm management and conservation, the concept of core and minicore collections have been advocated (Upadhyaya and Ortiz 2001), and trait-specific germplasm has been identified to aid breeding and genomics-assisted selection (Upadhyaya et al 2012). Further attempts were also made to characterise the chickpea germplasm at the molecular level in several studies (Iruela et al 2002;Croser et al 2003;Nguyen et al 2004;Rao et al 2007;Upadhyaya et al 2008;Sefera et al 2011;Choudhary et al 2012) separately from phenotypic characterisation (Upadhyaya et al 2012;Krishnamurthy et al 2013aKrishnamurthy et al , 2013b. Nevertheless, for understanding the genetics of complex traits like drought tolerance, trait mapping is essential for identifying the genes underlying drought tolerance.…”
Section: Genetic and Genomic Resourcesmentioning
confidence: 99%
“…지금 까지 Prunus dulcis의 RAPD 및 ISSR 분석 (Martins et al, 2004), Malus pumila의 RAPD 분석 (Modgil et al, 2005), Pinus thunbergii의 RAPD 분석 (Goto et al, 1998), 장기간 기 내 배양된 춘란(Cymbidium goeringii)과 한란(C. kanran)의 유전적 변이성 (Ryu et al, 2011 (Fang and Roose, 1997;Tsumura, 1996). 또한 AFLP (amplified fragment length polymorphism)보다 과정이 간단 하고 (Russel et al, 1997), RAPD보다는 primer 당 다형성 밴 드수가 더 많으며 (Iruela et al, 2002), primer들의 높은 결합 온도와 더 긴 서열 때문에 RAPD보다 정확하고 재현성이 우수한 밴드들이 생성되는 장점이 있다 (Esselman et al, 1999), 특히 ISSR이 목표로 하는 반복 서열은 진핵 게놈 전 체에 걸쳐 풍부하고 빠르게 변화하여 유전자 지문의 검출 에서 그 유용성이 입증되고 있다 (Godwin et al, 1997;Russel et al, 1997).…”
Section: 갈대(Phragmites Communisunclassified